Aberrant overexpression of HOTAIR inhibits abdominal adipogenesis through remodelling of genome-wide DNA methylation and transcription - Feng-Chih Kuo; Yu-Chun Huang; Ming-Ren Yen; Chien-Hsing Lee; Kuo-Feng Hsu; Hsiang-Yu Yang; Li-Wei Wu; Chieh-Hua Lu; Yu-Juei Hsu; Pao-Yang Chen (Elsevier, 2022)
Objective: Abdominal adiposity is strongly associated with diabetic and cardiovascular comorbidities. The long noncoding RNA HOTAIR (HOX Transcript Antisense Intergenic RNA) is an important epigenetic regulator with fat depot-specific expression. Its functional roles and epigenetic regulation in abdominal adipogenesis remain uncertain. Methods: We collected different fat depots from healthy, severely obese, and uraemic subjects to measure fat-depot specific gene expression and quantify regional adiposity via dual-energy X-ray absorptiometry (DXA). HOTAIR was overexpressed to evaluate its functional roles. Reduced representation bisulfite sequencing (RRBS), RNA-sequencing, real-time qPCR and RNA/chromatin immunoprecipitation were performed to analyse HOTAIR-mediated epigenetic regulation. Results: A negative correlation between adipose tissue HOTAIR expression (arm or abdominal subcutaneous fat depots) and regional adiposity under the status of severe obesity or uraemia was observed. HOTAIR overexpression using human immortalized abdominal preadipocytes further revealed its anti-adipogenic effects. Integrative analysis of genome-wide DNA methylation by reduced representation bisulfite sequencing (RRBS) and gene expression was performed. Overall, the differentially methylated genes were functionally enriched for nervous system development, suggesting that HOTAIR may be epigenetically associated with cell lineage commitment. We specifically found that HOTAIR-mediated genes showed strong changes in both DNA methylation and gene expression during abdominal adipogenesis. We observed that two HOTAIR-repressed genes, SLITRK4 and PITPNC1, present an obesity-driven fat-depot specific expression pattern that is positively correlated with the central body fat distribution. Conclusions: Our study indicated that HOTAIR is a key regulator of abdominal adipogenesis via intricate DNA methylation and is likely to be associated with the transcriptional regulation of genes involved in nervous system development and lipid metabolism, such as SLITRK4 and PITPNC1.